Space-Based Altimeter Backscatter Waveform Software Model - D. S. Borovitsky; A. E. Zhesterev; V. P. Ipatov; R. M. Mamchur (Известия высших учебных заведений России: Радиоэлектроника)
The subject of investigation is a space-based altimeter. The goal of investigation is development of MATLAB software model of echo-signal  in a satellite radar altimeter. The phenomenological treatment of a  scattering surface is used as a set of independent reflectors (specular  points) subject to a number of restrictions. The model produced is  applicable to simulating the effect of ranging signal parameters, antenna directivity, sea surface condition and other factors on the received  power profile as well as verification of theory inferences. The software  developed is of a great adequacy to physically predicted echo-signal  characteristics and quite suitable for computer experiments aimed at studying altimeter basic operation modes.